Cost-benefit analysis of aquaculture expansion in Arctic Norway - Aanesen, Margrethe; Mikkelsen, Eirik Inge (Aquaculture Economics & Management, 2019)
This is an Accepted Manuscript of an article published by Taylor & Francis in Aquaculture Economics & Management on 22 July 2019, available online: https://www.tandfonline.com/doi/full/10.1080/13657305.2019.1641570 . According to governmental plans, Norway faces huge expansions in the production of farmed Atlantic salmon. However, it is municipalities that designate coastal areas to aquaculture activities and their motivation depends on net benefits at municipal level from such use. Yet, there is little empirical evidence on costs and benefits of using coastal areas to aquaculture activities. We set up a cost-benefit analysis of salmon farming as seen from a municipal perspective. On the benefit side, we count consumer and producer surplus of increased aquaculture production in the region and the region’s share of the national rent in aquaculture received as transfers from the national Aquaculture Fund. Costs are the opportunity cost of the land (sea) use, measured by households’ willingness to pay to avoid aquaculture expansion, using data from a choice experiment. We find that parts of the producer surplus have to contribute to the regional economy for the NPV to be positive for a region.